Gender and conservation agriculture in sub-Saharan Africa: a systematic review. Issue 1 (2nd January 2019) - Wekesah, Frederick M.; Mutua, Edna N.; Izugbara, Chimaraoke O.
ABSTRACT: Conservation agriculture (CA) involves the practice of concurrent minimum tillage, permanent soil cover using crop residue, and crop rotation. Evidence indicates that CA increases agricultural productivity, reduces farming labour requirements, and improves soil quality. While CA is practised in several African contexts, little is known about its interaction with gender. This review synthesized knowledge on the interplay of gender and CA in sub-Saharan Africa. The review highlighted the relative neglect of gender issues in research on CA in SSA. Existing research was limited both in quantity and to a few countries in the region. There was also little critical focus on gender as a social phenomenon: a few of the studies conceptualized gender in terms of the socially constructed roles of men and women while the majority framed it in terms of the sexual categories of male and female. Compared to men, and due largely to gendered barriers, including lack of access to land; machinery; inputs; extension services; and credit facilities, women farmers adopted CA less and dis-adopted it more. CA increased women's incomes, labour involvement, household food security, as well as risks for land and crop dispossession by men when farming becomes lucrative. It also increased workloads, employment opportunities and health risks for women. CA positively altered gender relations, boosting women's participation in agricultural decision-making at the household level. Deliberately enlisting women as beneficiaries; working with men to advance their understanding of women's needs in agriculture; and offering agricultural inputs directly to women are some strategies that enhanced women's participation in CA. Gaps in current research on gender and CA include: critical focus on and understanding of gender as a social construct in relation to CA; the long-term impacts on CA for gender relations, incomes for men and women, and women's empowerment; the sustainability of strategies for supporting gendered participation in CA; and the dynamics of gendered access to local farmland markets for CA.